Representasi Gagasan Ekoteologi dalam Kumpulan Puisi Setelah Hari Keenam Karya Ahmad Nurullah - Rahmad Idea Tribisono; Akhmad Tabrani; Dyah Werdeningsih (Lembaga Teewan Journal Solutions, 2026)
This study aims to examine the ecotheological dimension in Ahmad Nurullah's poetry collection Setelah Hari Keenam by the Sixth Day, focusing on a reading that integrates ecocritical approaches and theological reflection. The research method used is qualitative analysis with an ecocritical approach based on an ecotheological perspective. The research data consist of poetic texts in Setelah Hari Keenam, which were purposively selected based on the relevance of their ecological and theological themes. The analysis was conducted by interpreting symbols, metaphors, and poetic structures to identify representations of nature, ecological submission, and spiritual reflections contained therein. The conclusion of this study is that Ahmad Nurullah's work functions not only as an aesthetic expression, but also as a theological-ecological text that encourages reconciliation between humans and the earth. An ecotheological reading of this work demonstrates the potential of literature in mediating spiritual relationships with nature and fostering collective awareness of the importance of environmental sustainability. This research is expected to expand the repertoire of Indonesian literary studies based on ecocriticism and become a reference for interdisciplinary research that connects literature, theology, and environmental studies.